Análise das rotas tecnológicas existentes para os resíduos sólidos urbanos no município de Cidade Ocidental/GO - Colvero, Diogo Appel (2014)
The treatment and final disposal of solid waste (MSW) have raised concern and been the subject of intense debate, especially after the Law nº 12.305 of 2 August of 2010 which established the National Policy of Solid Waste (BRASIL, 2010a) . This Law established that municipalities would have up to four years to give a final environmentally correct their waste, from its publication layout. However, in Goiás, only fourteen of the 246 municipalities in the state currently have a landfill licensed by the Department of the Environment and Water Resources, of Goiás State (DEWR/GO). Thinking about it, aimed a municipality in the state who possessed a system of allocation of their MSW that targets minimizing impacts to the environment. picked up Cidade Ocidental/GO, a municipality that is part of the Integrated Development Region of the Distrito Federal and Surrounding Areas (IDRSA/DF), which has two different technological routes for disposal of solid waste: the first route, part of that waste is collected selectively and sent to a central screening called Association of Workers in Recycling and Reuse of Waste (AWRRW) and; in the second route, the remaining waste is conventionally collected and sent to landfill, which is operated by a private company, with that receives not only MSW Cidade Ocidental but also of Valparaíso de Goiás/GO - neighboring municipality to the city in study - thus forming a unique system in Goiás landfill shared. This system complies with the PNRS, which suggests the formation of consortia/sharing between cities, as well as the government will prioritize resources to municipalities that seek to unite to give a destination to their MSW. The objective of this study was to evaluate the technical, economic and environmental aspects existing of technological routes MSW municipality of Cidade Ocidental. For this, we carried out desk research by collecting secondary data and primary data collection also about technological routes of MSW city in study. The first route, the selective collecting-sorting central is not shared, because covers only the municipality of Cidade Ocidental, around 33.550 people attended. The current cost to maintain this system is R$ 375,58 per ton collected . The second route, the conventional collection-landfill is shared, also attending Valparaíso de Goiás, with about 190.000 people contemplated. To collect of form conventional and dispose at the landfill, the concessionaire, which forms with prefecture of Cidade Ocidental a public-private partnership of municipalities charge R$ 156,55 per tonne. The route of selective collecting-sorting central has some problems, which if corrected, can serve as a model for other municipalities in the state. And the second route, the conventional collection-landfill, has problems in public-private partnership, because the landfill is not the infrastructure and operation under ideal conditions, besides being with the license unsuccessful operation. However, if the mismatches are corrected, the landfill shared is a viable alternative to the municipalities of the state of Goiás.